Residual Stresses in Composite Materials - Shokrieh, Mahmood (Woodhead Publishing Ltd., 2014)
Because of the increasing demand for high-strength, light-weight materials such as composites and their wide range of applications in the aerospace and automotive industries, in civil infrastructure and in sporting applications, it is critical that residual stresses of composite materials are understood and measured correctly. Topics include: destructive and non-destructive testing (NDT) techniques for measuring residual stresses; mathematical methods for calculation of residual stresses in composite materials; simulated hole drilling method; slitting/crack compliance method; measuring residual stresses in homogeneous and composite glass materials using photoelastic techniques; modeling residual stresses in composite materials; residual stresses in polymer matrix, metal-matrix and a range of other types of composites; addition of nanoparticles to the matrix of polymeric composites as a new technique for reduction of residual stresses. -- Edited summary from book.
Keywords: Polymeric composites.; elektronické knihy; electronic books